Analisis Korelasi Kemampuan Berbahasa Panah Dengan Kualitas Free-Body Diagram Siswa Pada Materi Dinamika - Pranata, Ogi Danika; Lorita, Evi (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
This study aims to analyze and determine the level of relationship between language of arrow skills with quality of free-body diagrams. The research was conducted at SMAN 2 Sungai Penuh. The population was 60 students of XI MIA. Using whole population sampling, but there were 6 incomplete data so only data from 54 students were used. The learning process and tests the language of arrow and quality of free-body diagrams were given to the students. The data is normally distributed and linearly related to each other with a positive correlation shown using a scatterplot. The Pearson correlation test conducted to show the relationship between variables. There is a high correlation between language of arrow skills and the quality of the free body diagram, which is indicated by the Pearson correlation coefficient of 0.611.